Enseignement transmissif, apprentissage actif : usages du podcasting par les étudiants universitaires - Nicolas Roland; Philippe Emplit (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Publishing audiovisual recordings of courses or complementary videos for students is not without asking some questions: how do students use these media? Is it a way of escaping classroom activities? What are the impacts on learning? Is it worth the teacher’s investment in time? The results of previous researches are inconsistent: some argue that podcasting has no significant effect, while others have concluded that it shows positive effects on results, motivation or anxiety. Complementing studies that consider that technologies are independent of individuals and contexts, our research takes a user-based approach in analysing how students integrate podcasting in their learning strategies. The research was conducted with students from twelve courses of the Université Libre de Bruxelles using a questionnaire (n= 2247), comprehensive interviews (n= 23) and an analysis grid of teaching devices. Crossing these data gives an understanding of the meaning of the podcasts for the students and the way that they use them to learn.